Integration of a smoking cessation program in the treatment protocol for patients with head and neck and lung cancer - de Bruin-Visser, J. C. (Springer-Verlag, 2011)
Smoking is the main causative factor for development of head and neck and lung cancer. In addition, other malignancies such as bladder, stomach, colorectal, kidney and pancreatic cancer have a causative relation with smoking. Continued smoking after having been diagnosed with cancer has many negative consequences: effectiveness of radiotherapy is diminished, survival time is shortened and risks of recurrence, second primary malignancies and treatment complications are increased. In view of the significant health consequences of continued smoking, therefore, additional support for patients to stop smoking seems a logical extension of the present treatment protocols for smoking-related cancers. For prospectively examining the effect of nursing-delivered smoking cessation programme for patients with head and neck or lung cancer, 145 patients with head and neck or lung cancer enrolled into this programme over a 2-year period. Information on smoking behaviour, using a structured, programme specific questionnaire, was collected at baseline, and after 6 and 12 months. At 6 months, 58 patients (40%) had stopped smoking and at 12 months, 48 patients (33%) still had refrained from smoking. There were no differences in smoking cessation results between patients with head and neck and lung cancer. The only significant factor predicting success was whether the patient had made earlier attempts to quit smoking. A nurse-managed smoking cessation programme for patients with head and neck or lung cancer shows favourable long-term success rates. It seems logical, therefore, to integrate such a programme in treatment protocols for smoking-related cancers.